2021
DOI: 10.1038/s41598-021-82153-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasound imaging for the assessment of normal versus steatotic livers

Abstract: Liver disease is increasing in prevalence across the globe. We present here a multiparametric ultrasound (mpUS) imaging approach for assessing nonalcoholic fatty liver disease (NALFD). This study was performed using rats (N = 21) that were fed either a control or methionine and choline deficient (MCD) diet. A mpUS imaging approach that includes H-scan ultrasound (US), shear wave elastography, and contrast-enhanced US measurements were then performed at 0 (baseline), 2, and 6 weeks. Thereafter, animals were eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Recently, it has been demonstrated that MPUS examinations have the potential to provide a comprehensive estimation of the main components of early-stage NAFLD [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that MPUS examinations have the potential to provide a comprehensive estimation of the main components of early-stage NAFLD [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, 3D data are best appreciated with the assistance of an interactive graphics tool and 3D displays. Furthermore, in many studies, we have more than three measured parameters, including first order statistics, shear wave elastography, and contrast parameters 16,19,20 . In these cases, we cannot directly visualize a higher multidimensional space, and so require a strategy for reducing these.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the M parameters can be directly used for imaging since SVM and inner product apply in a straightforward manner to M ‐dimensional inputs. Examples of multiparametric analysis ( M > 3) utilizing PCA and SVM are found in previous studies 16,19,20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations